Exploring the possibility of polycyclic aromatic hydrocarbons and fulleranes as the carrier of the 21 micron emission feature - Liao, Xuan-Xiang; Zhang, Yong; Sadjadi, SeyedAbdolreza (Frontiers in Astronomy and Space Sciences, 2024)
IntroductionThe 21 μm emission feature discovered in a small sample of carbon-rich protoplanetary nebulae has remained unidentified for over 30 years. A dozen of different molecular species (both organics and inorganics) have been proposed as the carrier candidates of this important feature, among which polycyclic aromatic hydrocarbons (PAHs) and fulleranes (hydrogenated fullerenes) have yet to be sufficiently examined.MethodIn this study, we attempt to fit the 21 μm features in observed spectra of the above-mentioned astronomical sources via theoretically simulated spectra of various PAHs and fulleranes, aiming to investigate whether the two hydrocarbon families can reproduce the 21 μm feature.Results and DiscussionBased on the fitting outcomes we conclude that fulleranes can provide a more plausible explanation for the origin of 21 μm feature than PAHs.